Maternity care with the Women's Business Service at the Mildura Aboriginal Health Service - Sandra Campbell; Stephanie Brown (Elsevier, 2004)
Abstract Objective:To assess and contrast views and experiences of women attending the Women's Business Service at the Mildura Aboriginal Health Service with those of rural women attending public maternity services who participated in a Victorian statewide survey conducted in 2000. Methods:Face‐to‐face interviews were conducted with clients of the Women's Business Service (n=25) using a structured interview schedule based on the Victorian Survey of Recent Mothers 2000. Comparisons were made with rural women who had participated in the 2000 survey and had received public care for their pregnancy (n=333). Results:Compared with rural participants in the 2000 survey, women who attended the Women's Business Service were significantly more likely to say care providers kept them informed (OR 20.63, 95% CI 3.27-853.75), midwives were never rushed during check‐ups (OR 22.24, 95% CI 3.50-921.47), and to say they were happy with medical care (OR 5.79, 95% CI 1.68-30.67). Eighty per cent of interview participants described their antenatal care as 'very good'. Fewer women rated intrapartum care (64%) or postnatal hospital care (43%) as 'very good'. Compared with rural participants in the statewide survey, women attending the Women's Business Service were significantly more confident about looking after their baby in the first week at home (OR 9.08, 95% CI 2.95-37.01), and less likely to want additional help or advice (OR 0.21, 95% CI 0.04-0.73). Conclusions:Women using the Women's Business Service were significantly more positive about many aspects of their care than women attending other rural public maternity services. The study lends support to the view that Aboriginal community‐controlled health services are well placed to provide appropriate and accessible care to Indigenous women.